Fundamentals of turbulent and multiphase combustion - Kuo, Kenneth K. (Wiley, 2012)
"This book is a follow-on to the author's bestseller, Principles of Combustion, Second Edition published in 2005. The text covers advanced topics of combustion and flame that are not covered anywhere else. Kuo provides a multiphase systems approach beginning with more common topics and moving to higher level applications such as reacting boundary layer flows, ignition of homogeneous mixtures, flame extinction phenomena, and detonation processes in condensed phase materials. As with Kuo's earlier book, large numbers of examples and problems and a solutions manual are provided"--